A Catalyst‐Free Amination of Functional Organolithium Reagents by Flow Chemistry. (8th March 2018) - Kim, Heejin; Yonekura, Yuya; Yoshida, Jun‐ichi
Abstract: Reported is the electrophilic amination of functional organolithium intermediates with well‐designed aminating reagents under mild reaction conditions using flow microreactors. The aminating reagents were optimized to achieve efficient C−N bond formation without using any catalyst. The electrophilic amination reactions of functionalized aryllithiums were successfully conducted under mild reaction conditions, within 1 minute, by using flow microreactors. The aminating reagent was also prepared by the flow method. Based on stopped‐flow NMR analysis, the reaction time for the preparation of the aminating reagent was quickly optimized without the necessity of work‐up. Integrated one‐flow synthesis consisting of the generation of an aryllithium, the preparation of an aminating reagent, and their combined reaction was successfully achieved to give the desired amine within 5 minutes of total reaction time.